Co-administration of plasmid-encoded granulocyte-macrophage colony-stimulating factor increases human immunodeficiency virus-1 DNA vaccine-induced polyfunctional CD4(+) T-cell responses - Santana, Vinicius Canato (Mem Inst Oswaldo Cruz, 2015)
T-cell based vaccines against human immunodeficiency virus (HIV) generate specific responses that may limit both transmission and disease progression by controlling viral load. Broad, polyfunctional, and cytotoxic CD4(+)T-cell responses have been associated with control of simian immunodeficiency virus/HIV-1 replication, supporting the inclusion of CD4(+) T-cell epitopes in vaccine formulations. Plasmid-encoded granulocyte-macrophage colony-stimulating factor (pGM-CSF) co-administration has been shown to induce potent CD4(+) T-cell responses and to promote accelerated priming and increased migration of antigen-specific CD4(+) T-cells. However, no study has shown whether co-immunisation with pGM-CSF enhances the number of vaccine-induced polyfunctional CD4(+) T-cells. Our group has previously developed a DNA vaccine encoding conserved, multiple human leukocyte antigen (HLA)-DR binding HIV-1 subtype B peptides, which elicited broad, polyfunctional and long-lived CD4(+) T-cell responses. Here, we show that pGM-CSF co-immunisation improved both magnitude and quality of vaccine-induced T-cell responses, particularly by increasing proliferating CD4(+) T-cells that produce simultaneously interferon-γ, tumour necrosis factor-α and interleukin-2. Thus, we believe that the use of pGM-CSF may be helpful for vaccine strategies focused on the activation of anti-HIV CD4(+) T-cell immunity.